2017
DOI: 10.1089/brain.2017.0509
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Salience Network and Its Subsystems with the Default-Mode and the Central-Executive Networks in Normal Aging and Mild Cognitive Impairment

Abstract: Previous functional magnetic resonance imaging (fMRI) investigations suggest that the intrinsically organized large-scale networks and the interaction between them might be crucial for cognitive activities. A triple network model, which consists of the default-mode network, salience network, and central-executive network, has been recently used to understand the connectivity patterns of the cognitively normal brains versus the brains with disorders. This model suggests that the salience network dynamically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
147
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(158 citation statements)
references
References 59 publications
8
147
0
3
Order By: Relevance
“…Increased activation in OA compared to YA may suggest reduced suppression of the DMN in OA, consistent with past work predicting increased DMN activity in OA relative to YA (Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Grady et al, 2010;Grady, Sarraf, Saverino, & Campbell, 2016). Taken together, the results presented here are compatible with previous work suggesting OA show an inability to correctly suppress the DMN during cognitive processing (Chand, Wu, Hajjar, & Qiu, 2017;Grady et al, 2010Grady et al, , 2016Raichle, 2015) and a seemingly reduced capacity to efficiently bring task-positive, error-correcting and attention-controlling brain regions online to update future responses (Langenecker & Nielson, 2003;Zhu, Zacks, & Slade, 2010). In line with these results, accuracy analyses showed OA are on par with YA by the second control block (a purely firstorder rule task), yet do not ever meet YA performance in second-order learning blocks.…”
Section: Discussionsupporting
confidence: 91%
“…Increased activation in OA compared to YA may suggest reduced suppression of the DMN in OA, consistent with past work predicting increased DMN activity in OA relative to YA (Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Grady et al, 2010;Grady, Sarraf, Saverino, & Campbell, 2016). Taken together, the results presented here are compatible with previous work suggesting OA show an inability to correctly suppress the DMN during cognitive processing (Chand, Wu, Hajjar, & Qiu, 2017;Grady et al, 2010Grady et al, , 2016Raichle, 2015) and a seemingly reduced capacity to efficiently bring task-positive, error-correcting and attention-controlling brain regions online to update future responses (Langenecker & Nielson, 2003;Zhu, Zacks, & Slade, 2010). In line with these results, accuracy analyses showed OA are on par with YA by the second control block (a purely firstorder rule task), yet do not ever meet YA performance in second-order learning blocks.…”
Section: Discussionsupporting
confidence: 91%
“…While as distinct functional networks, the ECN and the SN tended to share positive FC (He et al, ), consistent with their increased activation during cognitive tasks compared to the deactivated DMN. Past studies on healthy ageing have demonstrated the importance of the connectivity profile with the SN (Chand, Wu, Hajjar, & Qiu, ; Onoda, Ishihara, & Yamaguchi, ), for instance, by improving the classification success on episodic memory performance and executive function between young and old participants (La Corte et al, ). Lower ECN‐SN FC may suggest that APOE ‐ɛ4 carriers had aberrant communication between networks critical for externally oriented cognition compared to noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…It is potentially nontrivial to compare brain indices across scanners of different magnetic strength, and future research would benefit from assessing the extent to which these differences bias results in cross-cohort MRI studies. Finally, the neurostructural perspective is inherently limited in that it does not include functional information; since previous studies have found functional connections between several of the networks studied here 44 , our investigation, which treated networks separately, may have missed these links, which might explain additional cognitive variance over and above the properties of the individual networks. Integrating the structural and functional perspectives is a critical future task for network-focused cognitive neuroscience.…”
Section: Discussionmentioning
confidence: 96%
“…It is notable that elements within the Salience network were found to be relatively spared in late-life, implying that its trajectory across middle to older adulthood is flatter than other NOIs. Previous functional research has suggested that the Salience network acts as a control on other networks, such as the Central Executive and Default Mode networks, and that disruption of this control, or loss of functional connections between networks, is among the causes of cognitive decline 44,45,46 . Though we did not examine between-network connections here, our analyses did highlight the Central Executive network as being of particular interest for cognitive aging, despite it containing the fewest number of elements of any network.…”
Section: Discussionmentioning
confidence: 99%